2020
DOI: 10.3389/fphys.2020.00289
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia Enhances the Acute Stretch-Induced Increase in Calcium Spark Rate in Ventricular Myocytes

Abstract: In ventricular myocytes, spontaneous release of calcium (Ca 2+) from the sarcoplasmic reticulum via ryanodine receptors ("Ca 2+ sparks") is acutely increased by stretch, due to a stretch-induced increase of reactive oxygen species (ROS). In acute regional ischemia there is stretch of ischemic tissue, along with an increase in Ca 2+ spark rate and ROS production, each of which has been implicated in arrhythmogenesis. Yet, whether there is an impact of ischemia on the stretch-induced increase in Ca 2+ sparks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Late diastolic stretches, such as stretch pattern S, have been observed in various pathological conditions such as ischemia or heart failure (Neves et al, 2016 ) and isometric conditions are often used in experimental set-ups to immobilize the cells for optical mapping. In pathological conditions, such as ischemia, stretch is assumed to enhance calcium spark probability (Cameron et al, 2020 ), which may trigger calcium waves and DADs originating from these sites (Boyden et al, 2003 ; Boyden and ter Keurs, 2005 ; ter Keurs and Boyden, 2007 ). In addition to calcium waves, spontaneous contractile waves have been related to pro-arrhythmic effects in arrangements of weaker damaged regions in-series with normal muscle segments.…”
Section: Discussionmentioning
confidence: 99%
“…Late diastolic stretches, such as stretch pattern S, have been observed in various pathological conditions such as ischemia or heart failure (Neves et al, 2016 ) and isometric conditions are often used in experimental set-ups to immobilize the cells for optical mapping. In pathological conditions, such as ischemia, stretch is assumed to enhance calcium spark probability (Cameron et al, 2020 ), which may trigger calcium waves and DADs originating from these sites (Boyden et al, 2003 ; Boyden and ter Keurs, 2005 ; ter Keurs and Boyden, 2007 ). In addition to calcium waves, spontaneous contractile waves have been related to pro-arrhythmic effects in arrangements of weaker damaged regions in-series with normal muscle segments.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we assessed whether Ca 2+ release via RyR may be involved in the observed arrhythmogenic role of cytosolic Ca 2+ (like X-ROS, stretch-induced Ca 2+ -sparks are also enhanced by ischemia). 22 To test this, RyR in ischemic cells were stabilised in their closed state with dantrolene, however, this had no effect on arrhythmia incidence with stretch in diastole or the VP (Fig. 5a).…”
Section: Trpa1 Channels and Ros Mediate Ischemic Mechano-arrhythmogenicity During The Vpmentioning
confidence: 98%
“…4b). As fluorophore photoactivation is associated with the generation of ROS, 26 which is increased in ischemia, 22 ROS might also play a role in mechano-arrhythmogenicity in ischemic cells. To test this, we pre-incubated ischemic cells with NAC to chelate intracellular ROS and found that arrhythmia incidence in the VP decreased compared to ischemia alone (0.8 vs 6.8%; p<0.0005), with no effect in diastole (Fig.…”
Section: Trpa1 Channels and Ros Mediate Ischemic Mechano-arrhythmogenicity During The Vpmentioning
confidence: 99%
See 2 more Smart Citations